PERANAN KEPOLISIAN DALAM MENANGANI TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA YANG DILAKUKAN OLEH ANAK DI WILAYAH HUKUM KEPOLISIAN RESOR PELABUHAN BELAWAN - Darwin S. Pangaribuan; Muhammad Ansori Lubis; Syawal Amry Siregar (JURNAL PROINTEGRITA, 2021)
Child protection is all activities that can guarantee protection for children and guarantee their rights, such as living life from infancy to adulthood properly, and participating fully in accordance with human equality, as well as protection from coercive actions and discriminatory attitudes. However, criminal acts still involve children, such as in narcotics abuse. The abuse of narcotics has spread to children whose ability to think is still low, so they can quickly become involved in drug abuse, just because of the following factors to adults. It should be realized that in fact the most important factor that causes the child to be directly affected by the law because narcotics actually comes from outside himself, such as the lack of concern for parents (family) and environmental factors, relationships. The normative-empirical legal research method is used in the research. This is because the researcher uses statutory regulations as a study in solving problems, and the researcher also directly interviews related parties. The Belawan Harbor Resort Police has made efforts to make preventive (prevention) and repressive (prosecution) efforts in suppressing narcotics crimes, especially against children. Prevention efforts have been carried out in the form of socialization and legal counseling on narcotics abuse. This has been implemented in schools, universities, and the community in the Belawan Harbor Police area. So that the community, especially children, know the dangers of Narcotics in their lives. In terms of repressive efforts, the port resort police of Belawan have carried out examinations of children as narcotics abuse based on the law on the criminal justice system. This effort is in the form of diversion, namely rehabilitation or return to the parents. The implementation of regulations regarding the criminal justice system for children of narcotics abusers has not been fully implemented due to various obstacles in its implementation. Various factors, obstacles faced by the police in handling children who abuse narcotics are the behavior of child drug abusers, pressure on children from narcotics networks, short detention times for children, restrictions on diversion requirements, and rehabilitation as an effort to recover from drug abusers. which requires a long process